1982
DOI: 10.1007/bf00016661
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and long-term changes in surface cover of aquatic plants in a shallow pond, Ojaga-ike, Chiba, Japan

Abstract: Seasonal and long-term changes in surface cover of aquatic plants in a shallow pond, Abstract Seasonal changes in surface cover and long-term floral changes in aquatic plants of a shallow eutrophic pond, Ojaga-ike, as well as the phenology of each species, were studied . Out of ten floating-leaved and submerged plants, the following five species showed a change in surface cover during 1978 : Potamogeton crispus and Elodea nuttallii occupied 53 .5% of the total pond surface in May, Trapa natans and Nelumbo nuci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…The other type was the occurrence of mixed communities of submerged flora (two to three species) together with floating-leaved (one to two species) and emergent (one to four species) forms (Philipose et al 1970, Gopal 1990. As found in this study, the mixed occurrence of all growth forms has also been widely reported in other tropical and subtropical ponds (Kunii & Maeda 1982, Gopal & Chamanlal 1991, Hussainy 1965, Nasar & Dutta Munshi 1974, Pandey et al 1988, Kunii 1991, Zambrano et al 1999.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The other type was the occurrence of mixed communities of submerged flora (two to three species) together with floating-leaved (one to two species) and emergent (one to four species) forms (Philipose et al 1970, Gopal 1990. As found in this study, the mixed occurrence of all growth forms has also been widely reported in other tropical and subtropical ponds (Kunii & Maeda 1982, Gopal & Chamanlal 1991, Hussainy 1965, Nasar & Dutta Munshi 1974, Pandey et al 1988, Kunii 1991, Zambrano et al 1999.…”
Section: Discussionsupporting
confidence: 86%
“…Secchi disk visibility -The wide range of Secchi disk visibility values observed for V. spiralis ( Figure 1a) was similar to that reported by Kunii & Maeda (1982) for a subtropical pond with the same species as well as rich in other growth forms of aquatic vegetation. Thus tolerance of this species in low light is evident.…”
Section: Presence/absence Of Hydrophytessupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, we selected two overwintering species, P. crispus and E. nuttallii, as the pioneer species for the reestablishing. This is also because that these plants are typically rapid colonizers (Simons et al, 1994), have a particularly strong positive effect on water transparency compared to other macrophytes (Van Donk and Van de Bund, 2002), and are inclined to multiply under cool weather conditions in eutrophic waters (Kunii and Maeda, 1982). Hence, choosing winter and early spring with relatively high transparency and low water level for the reestablishing should be appropriate; (2) an optimized strategy for macrophyte planting was adopted via a combination of different species.…”
Section: Discussionmentioning
confidence: 99%
“…Kunt., and Ceratophyllum demersum L.) are found in abundance. Because of their competitiveness and adaptability, these species did not enable the development of other hydrophytes [33,34]. The above hydrophytes formed pure stands in our study site.…”
Section: Discussionmentioning
confidence: 89%